A Web-Based Prediction Model for Cancer-Specific Survival of Elderly Patients With Clear Cell Renal Cell Carcinoma: A Population-Based Study - Zhanghuang, Chenghao; Wang, Jinkui; Zhang, Zhaoxia; Jin, Liming; Tan, Xiaojun; Mi, Tao; Liu, Jiayan; Li, Mujie; He, Dawei (Frontiers in Public Health, 2022)
Background: Clear cell renal cell carcinoma (ccRCC) is expected in the elderly and poor prognosis. We aim to explore prognostic factors of ccRCC in the elderly and construct a nomogram to predict cancer-specific survival (CSS) in elderly patients with ccRCC. Methods: Clinicopathological information for all elderly patients with ccRCC from 2004 to 2018 was downloaded from the Surveillance, Epidemiology, and End Results (SEER) program. All patients were randomly assigned to a training set (70%) or a validation set (30%). Univariate and multivariate Cox regression model was used to identify the independent risk factors for CSS. A new nomogram to predict CSS at 1-, 3-, and 5- years in elderly patients with ccRCC based on independent risk factors. Subsequently, we used the consistency index (C-index), calibration curves and the area under the receiver operating curve (AUC) and decision curve analysis (DCA) to test the prediction accuracy of the model. Results: A total of 33,509 elderly patients with ccRCC were enrolled. Univariate and multivariate Cox regression analysis results showed that age, sex, race, marriage, tumour size, histological grade, TNM stage, and surgery were independent risk factors for CSS in elderly patients with ccRCC. We constructed a nomogram to predict CSS in elderly patients with ccRCC. The C-index of the training set and validation set were 0.81 (95%CI: 0.802-0.818) and 0.818 (95%CI: 0.806-0.830), respectively. The AUC of the training set and validation set also suggested that the prediction model had good accuracy. The calibration curve showed that the observed value of the prediction model was highly consistent with the predicted value. DCA showed good clinical application value of the nomogram. Conclusion: In this study, we explored prognostic factors in elderly patients with ccRCC. We found that age, sex, marriage, TNM stage, surgery, and tumour size were independent risk factors for CSS. We constructed a new nomogram to predict CSS in elderly patients with ccRCC with good accuracy and reliability, providing clinical guidance for patients and physicians.